Zloty – Poles’ National Identity Attribute? (Economic and Political Thought, 2010)
The article is an expression of interest in the attitude of the Polish societyafter the accession of Poland to the European Union. The announcementsmade by the government in connection with the introduction of the euroin Poland turned out to be an excellent research material relating to thePolish citizens’ reactions. When I was writing the article, I did not meetanybody with the Polish citizenship who would believe that the government’sannouncements regarding the introduction of the euro in Poland before 2013meant anything more than a promise that cannot be kept or, putting it morestraightforward, just a load of twaddle. The arguments soon faded away,the number of articles in the Polish press decreased and the headline “Euro2012” now appears only in sports news.The author’s main aim was to show the Polish society’s attitude towardsthe introduction of the euro in Poland. Before she did it, however, she outlinedthe history of the Polish currency. It did not turn out to be an entirely easytask. Although there are many works by outstanding writers on the historyof the Polish zloty, obtaining thorough knowledge about the attitude of thePoles towards the accession of Poland to the monetary union was a challenge.Fortunately, the Center for Public Opinion Research, the National Bank ofPoland and Tygodnik Powszechny, which developed an appendix Droga do euro(Route to the Euro) in 2009, did not let me down.Already in 2009 the dispute about the euro resembled the same oldstories. The cost-benefit analysis in relation to the substitution of the zlotyby the euro was discussed once again. Public debate had clearly politicalcharacter; social and cultural effects were not discussed, not to say they were– as usual – forgotten.Presenting the article during the 1st Political Science Congress inWarsaw, I had very few statistical data on the supporters and opponentsof the introduction of the common European currency in Poland and littleinformation about social and cultural effects of such an operation. It is mucheasier to write and speak about the effects of the introduction of the euro inGermany, France or Slovakia. In case of Poland such discussions seem to bepure conjectures, speculations that will have to wait for confirmation. Howlong? This question is also left without an answer at the moment.